Platelet releasate normalises the compromised muscle regeneration in a mouse model of hyperlipidaemia. Issue 3 (19th January 2021) - Barlow, Joseph; Sfyri, Pagona Panagiota; Mitchell, Rob; Verpoorten, Sandrine; Scully, David; Andreou, Charalampos; Papadopoulos, Petros; Patel, Ketan; Matsakas, Antonios
Abstract : New Findings: What is the central question of this study? What is the impact of obesity‐independent hyperlipidaemia on skeletal muscle stem cell function of ApoE‐deficient (ApoE –/– ) mice? What is the main finding and its importance? Compromised muscle stem cell function accounts for the impaired muscle regeneration in hyperlipidaemic ApoE –/– mice. Importantly, impaired muscle regeneration is normalised by administration of platelet releasate. Abstract: Muscle satellite cells are important stem cells for skeletal muscle regeneration and repair after injury. ApoE‐deficient mice, an established mouse model of hyperlipidaemia and atherosclerosis, show evidence of oxidative stress‐induced lesions and fat infiltration in skeletal muscle followed by impaired repair after injury. However, the mechanisms underpinning attenuated muscle regeneration remain to be fully defined. Key to addressing the latter is to understand the properties of muscle stem cells from ApoE‐deficient mice and their myogenic potential. Muscle stem cells from ApoE‐deficient mice were cultured both ex vivo (on single fibres) and in vitro (primary myoblasts) and their myogenic capacity was determined. Skeletal muscle regeneration was studied on days 5 and 10 after cardiotoxin injury. ApoE‐deficient muscle stem cells showed delayed activation and differentiation on single muscle fibres ex vivo . Impaired proliferation and differentiation profiles were also evident on isolated primary muscle stem cells in culture. ApoE‐deficient mice displayed impaired skeletal muscle regeneration after acute injury in vivo . Administration of platelet releasate in ApoE‐deficient mice reversed the deficits of muscle regeneration after acute injury to wild‐type levels. These findings indicate that muscle stem cell myogenic potential is perturbed in skeletal muscle of a mouse model of hyperlipidaemia. We propose that platelet releasate could be a therapeutic intervention for conditions with associated myopathy such as peripheral arterial disease. Abstract :